Decreased plasma acetaminophen glucuronide/acetaminophen concentration ratio warns the onset of acetaminophen‐induced liver injury. (17th May 2022) - Noda, Takumi; Kato, Ryuji; Ozato, Yasuyuki; Kawai, Yuka; Yamamoto, Masato; Kagawa, Yuya; Azuma, Misa; Yamamoto, Kojiro; Kusanagi, Mika; Uryu, Kiyoaki; Harada, Hiromasa; Ijiri, Yoshio; et al.
Abstract: Acetaminophen (APAP)‐induced liver injury (AILI) is the most common cause of acute liver failure. Although the mechanisms that trigger AILI are well known, it is less understood how to halt AILI progression and facilitate liver recovery. Therefore, it is necessary to understand the pathophysiology of APAP hepatotoxicity in patients and to examine predictive/preventive markers. In a clinical study, we had a case in which aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels increased in a patient with a low ratio of APAP glucuronide concentration (AP‐G)/APAP plasma concentration. Then a reverse translational study was conducted for clarifying this clinical question. The relationship between plasma AP‐G/APAP concentration ratio and the levels of AST and ALT was examined by in vivo and in vitro experiments. In in vivo experiments, 10‐week‐old rats showed lower UGT activity, lower AP‐G/APAP concentration ratios, and higher AST and ALT levels than 5‐week‐old rats. This suggests an inverse correlation between the AP‐G/APAP concentration ratio and the AST, ALT levels in APAP‐treated rats. Furthermore, as a result of the in vitro experiment, it was confirmed that the cell viability decreased when the AP‐G/APAP concentration ratio in the culture medium decreased. Since the decrease in the plasma AP‐G/APAP concentration ratio appears earlier than the increase of AST and ALT levels, the ratio might be a presymptomatic marker of AILI. When APAP is used for a long time, it is recommended to perform therapeutic drug monitoring of the AP‐G/APAP concentration ratio, which is a predictive/preventive marker of AILI. Abstract : Since the increase of deviant enzymes AST/ALT means that the acetaminophen (APAP)‐induced liver injury (AILI) has already developed, they are diagnostic markers. However, the change of APAP glucuronide concentration (AP‐G)/APAP ratio might be observed before the development of AILI. Therefore, plasma AP‐G/APAP concentrations might be the predictive/preventive marker of AILI and their monitoring is important.